2010
DOI: 10.1007/s00417-010-1437-3
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal imaging in inherited retinal disease using the technique of enhanced depth imaging optical coherence tomography

Abstract: Enhanced depth imaging using spectral domain OCT can be used to identify choroidal changes in inherited retinal disease. The pattern of choroidal change correlates well with the clinical appearance. It appears that the extent and pattern of choroidal thinning is dependent on the stage of the disease in some cases, and in others the causative gene defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
79
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 18 publications
8
79
1
3
Order By: Relevance
“…In a recent study of young Danish adults aged 20-29 years, the average SFCT was 344 mm. 6 Thus, our finding of a mean choroidal thickness of 327 mm in those aged [16][17][18][19] years suggests that choroidal thickness approaches the adult value at this age. Several cross-sectional studies in adults have clearly shown that choroidal thickness later decreases with advancing age; the mean decrease is 15-20 mm per decade in later life.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In a recent study of young Danish adults aged 20-29 years, the average SFCT was 344 mm. 6 Thus, our finding of a mean choroidal thickness of 327 mm in those aged [16][17][18][19] years suggests that choroidal thickness approaches the adult value at this age. Several cross-sectional studies in adults have clearly shown that choroidal thickness later decreases with advancing age; the mean decrease is 15-20 mm per decade in later life.…”
Section: Discussionmentioning
confidence: 65%
“…In high myopia, retinal dystrophy, and age-related choroidal atrophy, the choroid was reported to have decreased thickness, whereas increased choroidal thickness was reported in central serous chorioretinopathy and Vogt-Koyanagi-Harada disease. [15][16][17][18][19] Also, there is recent data on the hemodynamic effect of chemicals-sildenafil and nicotine-on choroid, obtained by OCT. 20,21 In our population of 160 patients aged 4-23 years, we found a mean SFCT of 308 mm with substantial variation between individuals, which was consistent with previous studies in adults. 4,22 Recent studies examining in vivo choroidal thickness with OCT in children have reported mean SFCT values of 348 mm (in 48 Korean children aged 4-10 years), 9 330 mm (in 194 children aged 4-12 years), 10 and 342 mm (in 174 children aged 3.5-15 years).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced depth imaging (EDI) technology has led to a revolution in the study of deeper eye structures, such as the choroid and the LC. [4][5][6] It allows visualisation of the LC underneath the neuroretinal ring and provides high resolution images similar to those obtained by histology. This technique has been used to evaluate the LC in both normal and glaucomatous subjects.…”
Section: Introductionmentioning
confidence: 98%
“…[8][9][10][11] The new technology has lead to better understanding of the role of choroid in various macular diseases, including central serious chorioretinopathy, 9-11 high myopia, 12,13 Vogt-Koyanagi-Harada disease, 14 and a variety of retinal dystrophies. 15 However, although SD-OCT has been used to assess choroidal thickness in various diseases, including AMD, it has not yet been used to correlate choroidal thickness with drusen load in dry AMD.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] The new technology has lead to better understanding of the role of choroid in various macular diseases, including central serious chorioretinopathy, 9-11 high myopia, 12,13 Vogt-Koyanagi-Harada disease, 14 and a variety of retinal dystrophies. 15 However, although SD-OCT has been used to assess choroidal thickness in various diseases, including AMD, it has not yet been used to correlate choroidal thickness with drusen load in dry AMD.In addition to measuring choroidal thickness, SD-OCT can now be used to measure drusen load (area and volume). This novel diagnostic technology and algorithm was evaluated and showed the ability to generate highly reproducible qualitative and quantitative analysis of the drusen area and volume.…”
mentioning
confidence: 99%